Consumption patterns of boarding students - Rahmandhita Aulia Lubiyansyah (Indonesian Journal of Social Sciences, 2020)
Boarding house students are students who migrate. Their consumption patterns are determined by the income they receive each month. The consumption of boarding students, among others, is for food consumption and nonfood consumption. This study aims to analyze the consumption patterns of boarding house students from the class of 2017 in the Department of Anthropology, Airlangga University. The data of this study were obtained from the questionnaire (primary) and interviews with boarding house students from the class of 2017 in the Department of Anthropology, Airlangga University. The results of this study showed that the high income students tend to be more consumptive compared to the lower income ones.